Pengembangan Multimedia Interaktif Android Pembelajaran Sistem Pengapian DLI Peserta Didik Kelas XI SMK Muhammadiyah Bligo - Setiawan, Irman; Kurniawan, Adhetya (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to develop Android-based interactive multimedia in Distributor Less Ignition System (DLI) learning to improve student learning outcomes. The research method used is research and development with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research population included all students of class XI of SMK Muhammadiyah Bligo, with a purposive sampling technique involving two classes totaling 70 students. Data collection instruments include learning outcome tests and student response questionnaires. The results of the media feasibility test showed that the assessment by media experts was 88% and by material experts by 90%, both of which were in the "very feasible" category. The implementation was carried out in two classes, namely the experimental class that uses Android-based interactive multimedia, and the control class that uses conventional methods. The results of the t-test (independent sample t-test) showed a value of sig. (2-tailed) = 0.001 (p < 0.05), which means that there is a significant difference between the learning outcomes of students in the experimental class (mean = 86.7) and the control class (mean = 74.3). Educators' and learners' responses to multimedia use received scores of 92% and 91%, respectively, in the "very feasible" category. Based on these findings, it can be concluded that Android-based interactive multimedia developed using Lectora Inspire software has proven to be effective and feasible to be used as a learning medium to improve students' learning outcomes on the basic competencies of the DLI ignition system in vocational high schools.